The Influence of Digital Marketing and Brand Awareness on Purchase Decisions for Local Micro Small and Medium Enterprises Fashion Brands in Post-New Normal Bandung City - Sukma, Andhi; Iswara, Viona Duta (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
This study aims to analyze and identify internet advertising and electronic word of mouth on purchasing decisions on the GoTo e-commerce site for consumers who use courier services. This research is expected to be a reference from other parties, and can also be used as literature for further research by providing a form of information related to the variables of Internet Advertising and Electronic Word Of Mouth in purchasing decisions on the GoTo online shop site. The sample in this study is consumers who use courier services. The sample is 100 people. This type of research is an explanatory research using a quantitative approach. Sources of data used in this study are primary data. Data was collected by distributing questionnaires. The data analysis and hypothesis testing techniques used were multiple linear regression, validity, reliability, normality, partial test (t test), simultaneous test (f test), and coefficient of determination. The program used in analyzing the data uses the Statistical Package for Social Sciences (SPSS). The results of this study indicate that Internet Advertising and Electronic Word Of Mouth (EWOM) have a simultaneous effect on purchasing decisions.   Keywords: Internet advertising, EWOM, purchasing decisions.